Review of Research on Nuclear Signal Pulse Shaping - Tang, Zhihe; Liu, Zewei (Journal of Theory and Practice of Engineering Science, 2024)
Pulse shaping can greatly improve the signal-to-noise ratio and has been widely used in nuclear signal processing. This paper gives a brief overview of the current research status of nuclear signal pulse shaping at home and abroad. It describes in detail the three traditional pulse shaping methods of quasi-Gaussian shaping, triangular shaping and trapezoidal shaping, and discusses the nuclear pulse signal shaping that has appeared in recent years. And a brief introduction to the nuclear pulse signal shaping methods that have emerged in recent years is also given.